Pengaruh Konsentrasi Pupuk Lemna Minor terhadap Populasi Dunaliella salina [Effect Of Lemna Minor Fertilizer Concentration On Dunaliella salina Population] - Boedi S. Rahardja; Tjokorde Astrid S; Endang Dwi Masithah (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Dunaliella salina is a microalgae that have a high nutrient content, ctherefore Dunaliella salina widely used as an effective natural food, because they have cell walls and is easily digested. Dunaliella salina is rich in phytoplankton nutrients such as omega 3 and omega 6 and essential amino acids. Dunaliella salina has a large potential for the amount of β-carotene and glycerol. Lemna minor in addition containing nutrient n and p high also has a high concentration of minerals and pigment, especially beta carotene and xantofil so either for growth Dunaliella salina. This research aimed to know the effect of fertilizers on the growth of Lemna minor populations of Dunaliella salina and the optimal concentration of fertilizer Lemna minor in Dunaliella salina culture. Lemna minor doses used in this research are A (0 ml/l), B (0.25 ml/l), C (0.5 ml/l), D (0.75 ml/l), E (1 ml/l) and the use of fertilizers walne (1 ml/l) as with the control for the research. This research method is experimental methods. Research was done at the Faculty of Fisheries and Marine Laboratory, University of Airlangga for 7 days. The main parameter was observed the population Dunaliella salina. Supporting parameter includes water quality. The results suggest the best dose of fertilizer Lemna minor for the growth of Dunaliella salina is the dose in treatment D (0.75 ml/l) of 36.18x104 cells/ml, the highest growth occurred on the fifth day. Based on measurements of water quality throughout the treatment is still decent and good to support the the growth of Dunaliella salina during the research.